2015
DOI: 10.1080/19490976.2014.1000080
|View full text |Cite
|
Sign up to set email alerts
|

Inferred metagenomic comparison of mucosal and fecal microbiota from individuals undergoing routine screening colonoscopy reveals similar differences observed during active inflammation

Abstract: The mucosal microbiota lives in close proximity with the intestinal epithelium and may interact more directly with the host immune system than the luminal/fecal bacteria. The availability of nutrients in the mucus layer of the epithelium is also very different from the gut lumen environment. Inferred metagenomic analysis for microbial function of the mucosal microbiota is possible by PICRUSt. We recently found that by using this approach, actively inflamed tissue of ulcerative colitis (UC) patients have mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…12545758 Additionally, epithelial cell function is affected to a greater extent by mucosally associated microbes 5961 as measured herein, functional differences have been observed between mucosal and luminal microbiota, 62 and mucosal but not faecal microbiota may discriminate between disease status and health. 60 …”
Section: Discussionmentioning
confidence: 64%
“…12545758 Additionally, epithelial cell function is affected to a greater extent by mucosally associated microbes 5961 as measured herein, functional differences have been observed between mucosal and luminal microbiota, 62 and mucosal but not faecal microbiota may discriminate between disease status and health. 60 …”
Section: Discussionmentioning
confidence: 64%
“…It is known that the microbial composition between stool and mucus is significantly different . For example, one study showed that mucus samples had a greater relative abundance of Proteobacteria and Fusobacteria than stool, although the stool had a greater proportion of Firmicutes and Bacteroidetes . Taken together, these data emphasize the need to investigate the different microbial niches within the gut, to comprehensively explore the gut microbiota and the impact of genotype or environment.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially further studies should consider niche as both our qPCR and DGGE analysis of stool, colonic and small intestinal mucus highlighted differences in the microbial population among those niches. It is known that the microbial composition between stool and mucus is significantly different . For example, one study showed that mucus samples had a greater relative abundance of Proteobacteria and Fusobacteria than stool, although the stool had a greater proportion of Firmicutes and Bacteroidetes .…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies from the Mucosal Immunity of Ulcerative Colitis Patients Undergoing Therapy With Trichuris Suis Ova (MUCUS) (Trial ID: NCT01433471, https://clinicaltrials.gov) were collected from two trial subjects (ENR1 and ENR3) at three different time points (baseline, week 12 and week 24 post-treatment). Non-IBD control biopsies of the ileum and the sigmoid colon were obtained from patients referred to the Gastroenterology clinic at the Manhattan campus of the Veteran Affairs Hospital for average risk screening colonoscopy (19, 20). All FACS and 16S rRNA sequencing data were generated as previously described in (17).…”
Section: Methodsmentioning
confidence: 99%